A systematic review and computational modelling analysis of unilateral montages in electroconvulsive therapy. (4th September 2019) - Martin, D.; Lin, F.; Bai, S.; Moffa, A.; Taylor, R.; Nikolin, S.; Bull, M.; Dokos, S.; Loo, C. K.
Abstract : Objective: To examine the clinical outcomes of ECT unilateral placements compared in prior studies and apply insights from computational modelling to understand differences between placements. Methods: PubMed, Embase, Scopus and PsycINFO and reference lists were systematically searched for studies of depressed patients where two unilateral placements were compared and clinical outcomes were reported. Computational modelling was done to generate electric field maps for each unilateral placement identified in the systematic review. Results: A total of 29 studies met criteria for inclusion. Eight studies reported efficacy outcomes and 23 studies reported cognitive outcomes. Most studies found no significant difference in efficacy between right unilateral (RUL) and left unilateral (LUL) ECT, and no difference was found between temporo‐parietal and fronto‐temporal ECT. For the majority of studies, RUL placements had better verbal anterograde memory outcomes compared with the LUL placements. There was some evidence suggestive of cognitive advantages for fronto‐frontal and fronto‐parietal placements relative to temporo‐parietal ECT. Conclusions: For efficacy, studies mainly focused on the comparison of right vs. left hemispheric stimulation, with the available evidence suggesting no substantive difference. RUL placements tended to have better verbal anterograde memory outcomes relative to LUL placements, though limited differences were found between the RUL placements.